Forskolin Protected against Streptozotocin-Induced Diabetic Cardiomyopathy via Inhibition of Oxidative Stress and Cardiac Fibrosis in Mice. (30th January 2021) - Zhang, Xu; Ke, Pei-Xiong; Yuan, Xun; Zhang, Gui-Ping; Chen, Wen-Liang; Zhang, Gen-Shui
Abstract : Background . Diabetic cardiomyopathy is one of the cardiac complications in diabetes patients, eventually resulting in heart failure and increasing morbidity and mortality. Oxidative stress is a critical pathological feature in diabetic hearts, contributing to the development of DCM. Forskolin (FSK) was shown to reduce oxidative stress. This study was aimed at investigating the effects of FSK on diabetic hearts and the relevant molecular mechanisms. Methods . Streptozotocin- (STZ-) induced diabetes in mice was treated with FSK through intraperitoneal injection. Cardiac functions were evaluated by echocardiography. Hematoxylin-eosin and Masson trichrome staining was employed to determine heart morphological changes and cardiac fibrosis, respectively. Cardiac fibrosis-related markers were detected by western blot. Superoxide dismutase activity, reduced/oxidized glutathione ratio, and malondialdehyde concentration in left ventricles were determined using respective commercial kits. Results . Abnormal cardiac diastolic dysfunction and cardiac fibrosis were observed in diabetic hearts. FSK treatment significantly improved the cardiac diastolic function and attenuated the abnormal morphological change in diabetic hearts. Moreover, FSK treatment in diabetic mice decreased the expression of fibronectin, collagen I, TGF- β, and α -SMA and reduced myocardial fibrosis. Furthermore, we observed that FSK significantly blocked oxidative stress in diabetic hearts. Conclusions . Our study demonstrates that FSK protects against the development of DCM in STZ-induced diabetes in mice. Our study suggests that FSK might be a potential target for drug development in treating DCM.